Gentiopicroside Ameliorates Diabetic Renal Tubulointerstitial Fibrosis via Inhibiting the AT1R/CK2/NF-κB Pathway - Xu, Zhanchi; Zhang, Meng; Wang, Yu; Chen, Rui; Xu, Shiyue; Sun, Xiaohong; Yang, Yan; Lin, Zeyuan; Wang, Shaogui; Huang, Heqing (Frontiers in Pharmacology, 2022)
Renal tubulointerstitial fibrosis (TIF), characterized by epithelial-to-mesenchymal transition (EMT) of renal tubular epithelial cells, is the typical pathological alteration in diabetic nephropathy. Gentiopicroside (GPS), a natural compound with anti-inflammatory activity, has been demonstrated to alleviate glomerulosclerosis, whereas whether GPS inhibits TIF via regulating inflammation remains unclear. In this study, diabetic db/db mice and high glucose (HG)-stimulated renal tubular epithelial cells (NRK-52E) were applied to explore the effects and mechanisms of GPS on TIF. The results in vivo showed that GPS effectively improves glycolipid metabolism disorder, renal dysfunction, and TIF. In particular, GPS treatment reversed the abnormal expressions of EMT marker proteins including elevated α-smooth muscle actin and vimentin and decreased E-cadherin in the kidney of db/db mice. Moreover, GPS treatment also inhibited protein expressions of angiotensinⅡ type 1 receptor (AT1R) and CK2α and the activation of the NF-κB pathway. Importantly, the aforementioned effects of GPS acted in vivo were further observed in vitro in HG-stimulated NRK-52E cells, which were independent of its effects on glucose and lipid-lowering activity but were reversed by AT1R over-expression. Together, our results indicate that GPS that directly inhibits the CK2/NF-κB inflammatory signaling pathway via AT1R may also contribute to the amelioration of TIF in diabetes.